2021
DOI: 10.1093/conphys/coab058
|View full text |Cite
|
Sign up to set email alerts
|

Does hydrostatic pressure influence lumpfish (Cyclopterus lumpus) heart rate and its response to environmental challenges?

Abstract: Studies on the effects of environmental changes with increasing depth (e.g. temperature and oxygen level) on fish physiology rarely consider how hydrostatic pressure might influence the observed responses. In this study, lumpfish (Cyclopterus lumpus, 200–400 g), which can exhibit vertical migrations of over 100 m daily and can be found at depths of 500 m or more, were implanted with Star-Oddi micro-HRT loggers. Then, their heart rate (fH) was measured in a pressure chamber when exposed to the following: (i) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…However, this was unlikely to have been the cause of the salmon mortalities in this study as the surgeon (Z.A.Z.) had considerable experience (see Zrini and Gamperl, 2021 ; Zrini et al, 2021 ) and surgical times were short (average 12 min). That said, recovery location might have been a contributing factor.…”
Section: Discussionmentioning
confidence: 91%
“…However, this was unlikely to have been the cause of the salmon mortalities in this study as the surgeon (Z.A.Z.) had considerable experience (see Zrini and Gamperl, 2021 ; Zrini et al, 2021 ) and surgical times were short (average 12 min). That said, recovery location might have been a contributing factor.…”
Section: Discussionmentioning
confidence: 91%
“…These animals are cold blooded and thus the environmental temperature has a substantial impact on their physiology. Heart rate measurements in response to increased temperature and exercise demonstrated that lumpfish have a relatively poor response with a low maximal heart rate and thus these fish are unlikely to perform well under conditions when temperatures rise ( Zrini, Sandrelli & Gamperl, 2021 ). Preference studies show adult lumpfish prefer 6–7 °C but on land production of these animals is typically 10 °C ( Mortensen et al, 2020 ).…”
Section: Lumpfish Welfarementioning
confidence: 99%
“…Winter flounder ( Pseudopleuronectes americanus ) exhibits hypoxic bradycardia at 8 but not 15°C 133 . It was recently shown in lumpfish ( Cyclopterus lumpus ) that mild hypoxia results in a small increase in heart rate, although this was prevented by elevated hydrostatic pressure simulating increased water depth 134 . In carp ( Cyprinus carpio ), moderate hypoxia is met with an initial tachycardia which then declines, but only to resting levels 13 .…”
Section: The Regulation Of Heart Rate In Fishes Exposed To Hypoxiamentioning
confidence: 99%
“…133 It was recently shown in lumpfish (Cyclopterus lumpus) that mild hypoxia results in a small increase in heart rate, although this was prevented by elevated hydrostatic pressure simulating increased water depth. 134 In carp (Cyprinus carpio), moderate hypoxia is met with an initial tachycardia which then declines, but only to resting levels. 13 In rainbow trout (Oncorhynchus mykiss), perhaps the most well studied of all teleost fishes in comparative physiology (at least before the emergence of zebrafish as a model organism), both classic [135][136][137] and more recent 138 studies have described the archetypal piscine hypoxic bradycardia.…”
Section: Adultsmentioning
confidence: 99%